Borderline or locally advanced pancreatic adenocarcinoma: A single center experience on the FOLFIRINOX induction regimen. Issue 8 (August 2020) - Garnier, Jonathan; Ewald, Jacques; Marchese, Ugo; Gilabert, Marine; Moureau-Zabotto, Laurence; Giovannini, Marc; Poizat, Flora; Delpero, Jean-Robert; Turrini, Olivier
Abstract: Introduction: This study aimed to determine the impact of FOLFIRINOX neoadjuvant therapy on patients with non-metastatic borderline/locally advanced (BL/LA) pancreatic ductal adenocarcinoma (PDAC), in current practice. Material and methods: From 2010 to 2017, 258 patients with BL/LA PDAC from a single high-volume institution received FOLFIRINOX neoadjuvant treatment. Results: The 258 patients received a median number of 6 cycles of FOLFIRINOX (range, 3–16); 98 (38%) patients underwent curative surgery, and 160 (62%) continued medical treatment. A venous resection was performed in 57 patients (58%), and an arterial resection in 12 (12%). The postoperative 30- and 90-day mortality rates were 6.1% and 8.2%, respectively. Adjuvant chemotherapy was performed in 57 patients (59%). The median overall survival (OS) in patients who did (n = 98) or did not (n = 160) undergo surgical resection were 39 months and 19 months, respectively ( P  < 0.001). In resected patients, the ASA 3 score ( P  < 0.01), venous resection ( P  < 0.01), hemorrhage ( P  < 0.01), and R1 margin status ( P  = 0.03) were found to negatively influence the OS. The median OS was significantly higher in patients who did not require a venous resection (not reached vs. 26.5 months, P  < 0.001). Conclusions: Neoadjuvant FOLFIRINOX provided a survival benefit in BL/LA PDAC patients, particularly in those who did not ultimately require venous resection.